Extended characterization of damage in rubble mound scour protections - Tiago Ferradosa (2020)
The analysis of damage in rubble mound scour protections is crucial for the armour stability assessment. Former methodologies focused on the analysis of the maximum damage number. This work introduces a complementary methodology to determine and characterize damage statistical distribution based on a flexible arrangement of sub-areas. The sub-areas are overlapping and can be varied in size, allowing a refined damage analysis. To capture the variation of damage with changing sub-area layout, the methodology is coupled with a statistical evaluation of damage numbers, which is enabled by the definition of a grid ratio between armour stone size and sub-area size, (D-n50)(2)/A(sub). The methodology is applied to high resolution bathymetric surveys from two stability tests of large-scale rip-rap scour protection around a monopile foundation and combined wave and current loading. Results show that the methodology provides a complementary understanding of damage distribution to the maximum damage acquired from previous methodologies. In addition, it allows a comparison of damage characteristics between tests despite different shapes of the foundation. Research concludes that the size of the sub-areas influences significantly the damage description. Characteristic measures as the maximum damage number and standard deviation become stable at a grid ratio (D-n50)(2)/A(sub) equal to 1/4.